(untitled) (Third Sector Social Economic Review, 2020)
The importance of global value chains, increasing information communication technology and developing infrastructure have reached higher levels for countries. Participation in global value chains and the contribution of values obtained from this participation to countries are expressed as achieving sustainable development, growth, prosperity and international competitiveness. The need for these two important issues to be addressed together was observed as the international competition increased and global trade shifted towards global value chains trade. Therefore, this study aims to reveal the causal relationship between global value chains and competitiveness. In the study, data from 51 countries were used between 2007 and 2015 for analysis. The variables used in the analysis were obtained from the OECD, World Bank and World Economic Forum database. Participation of countries in global value chains is handled with 2 different variables as backward participation and forward participation, and it is aimed to analyze causality relations with international competitiveness. According to the results of panel cointegration tests, panel var tests and panel causality tests, it has been observed that there is a one-way causality relationship from forward participation to international competitiveness.